Development of a Community-Based Care Model for Chronic Psychiatric Patients in Phu Ruea District, Loei Province, Thailand - chutanawaropakon, Kanitta (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
Community-based mental health care remains inadequate in rural Thailand, with psychiatric patients experiencing poor medication adherence, inadequate family support, and community stigma. Current hospital-centered care models fail to address comprehensive community needs for chronic psychiatric patients. To develop and evaluate the effectiveness of a community-based care model for chronic psychiatric patients in Phu Ruea District, Loei Province, Thailand. This research and development study employed a four-phase approach conducted from May 2024 to May 2025. Phase 1 involved problem assessment through home visits and in-depth interviews with 194 psychiatric patients and 30 stakeholders. Phase 2 utilized focus group discussions with 37 multidisciplinary team members to develop the care model. Phase 3 implemented a pilot study with 30 patients followed by full-scale implementation with 58 chronic psychiatric patients and their caregivers for three months. Phase 4 evaluated outcomes using standardized instruments including the Brief Psychiatric Rating Scale (BPRS), Global Assessment of Functioning (GAF) Scale, and WHO Quality of Life Brief Thai Version (WHOQOL-BREF-THAI). Data were analyzed using descriptive statistics and paired t-tests. The developed model comprised four components: (1) establishing psychiatric care as a district priority through the District Health Board, (2) implementing a color-coded patient classification system for community follow-up, (3) conducting health education campaigns through online media and community broadcasting focusing on five warning signs, and (4) training caregivers and community members. Post-implementation evaluation showed significant improvements (p < 0.001): reduced psychiatric symptoms (mean difference = 14.24 points, t = 14.24), improved functional capacity (mean difference = 8.05 points, t = 7.83), enhanced quality of life (mean difference = 6.98 points, t = 7.26), and increased caregiver knowledge (mean difference = 13.99 points, t = 11.93). The community-based care model significantly improved psychiatric symptoms, functional capacity, and quality of life among chronic psychiatric patients while enhancing caregiver knowledge and skills. This collaborative, multi-sectoral approach demonstrates potential for sustainable community mental health care in rural settings.